Menganalisis Digital Marketing Sebagai Alat Strategi Pemasaran UMKM di Era Revolusi Digital - Jumaati; Nurhaerah; Muh Taftazani JR (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the implementation of digital marketing as a strategic tool in the digital revolution era. The research was conducted at the Arsyla Collection shop, located on Jalan Andi Makkasau, Mamuju Regency. A qualitative descriptive method—specifically a naturalistic inquiry approach—was employed, utilizing a series of interviews and observations; the informants included the shop owner (owner of Arsyla Collection) and an administrative/editing assistant. The findings indicate that the digital marketing revolution offers significant benefits for MSMEs, as digital marketing entails relatively low costs and enables a wider market reach without requiring extensive time for in-person (offline) promotions. Furthermore, adopting a digital marketing strategy centered on content creation effectively attracts potential customers, increases brand awareness, builds audience trust and loyalty, engages emotions, expands audience reach, and boosts sales in a precise and effective manner.